THE POLITICAL INFORMATIONAL ONTOS AS A RESULT OF THE GRAVITY FACTORS INFLUENCE ON COMMUNICATION PROCESSES - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The socio-philosophic investigation of the social gravity phenomenon is carried out and the character of its influence on political informational ontos is defined